Communicative Leadership in Digital Organizations: Rethinking Management Principles in the Age of Social Media - Rahmawati Novaria; Nara Garini Ayuningrum; Ana Nahdiah Irfani; Beta Puspitaning Ayodiya (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN-COMMUNITY OF RESEARCH LABORATORY, 2025)
The rapid expansion of digital technologies and social media has fundamentally transformed organizational communication and managerial practices. Traditional management principles—particularly those related to leadership, coordination, and decision-making—are increasingly challenged by decentralized, networked, and participatory communication environments. This study explores how communicative leadership is redefined within digital organizations, emphasizing the role of interaction, discourse, and mediated communication in shaping managerial authority. Drawing on organizational communication theory and leadership studies, particularly the work of Henry Mintzberg and Manuel Castells, this research employs a qualitative approach through discourse analysis of digital organizational practices and communication patterns on social media platforms. The findings reveal that leadership is no longer centered on hierarchical control but is increasingly constructed through communicative engagement, visibility, and responsiveness. The study argues that communicative leadership in digital contexts requires a shift from command-based authority to relational and dialogic practices, where meaning-making and influence emerge through continuous interaction. This research contributes to the rethinking of foundational management concepts by situating them within the dynamics of digital communication and networked organizational structures.